ANALOGI PEREMPUAN DALAM PERKEMBANGAN ARSITEKTUR VERNAKULAR DI SULAWESI SELATAN - Andi Hildayanti (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2022)
In the vernacular architecture development, the female body size has been used as a basis for determining the room size in the building. The existing forms appreciation manifested in domain forms, space functions, materials, and ornaments. The female gender elements, both in terms of body anatomy and  special room, are applied as a form of reflection the traditional identity house. One of the traditional houses that applies gender roles as an architectural philosophy is the Karampuang Traditional House which is located in Sinjai Regency, South Sulawesi. This study discusses the role of women as the basis for the philosophy and architectural symbolism of the Karampuang Traditional House. The analytical method used is descriptive analysis interpretation based on the architectural components found in the Karampuang house data. The results showed that complexity of female gender which cannot be separated from the nature of women and the history of Karampuang where the first person to build and prosper Karampuang is a woman. The use and placement of symbols on parts and ornaments of the house represents the female body anatomy. The female gender is more dominant in the traditional Karampuang house. Aspects based on gender in the Karampuang traditional house are influenced by the history believed by the community, and female gender elements both in terms of body anatomy, as well as a special room for women are applied in their traditional houses. In the context of preserving traditional houses and regional culture, especially in Karampuang, serious attention is needed both by the people themselves and by the government in an effort to protect, maintain, and maintain the uniqueness of Karampuang architecture.